Psychosocial Attributes of Housing and Their Relationship With Health Among Refugee and Asylum-Seeking Populations in High-Income Countries: Systematic Review - Tessa-Maria Brake; Verena Dudek; Odile Sauzet; Oliver Razum (Frontiers Media S.A., 2023)
Objectives: Housing as a social determinant of health should provide not only shelter, but also a feeling of home. We explored psychosocial pathways creating a sense of home and influencing the relationship between housing and health among asylum seekers and refugees (ASR) in high-income countries.Methods: We performed a systematic review. To be included, studies had to be peer-reviewed, published between 1995 and 2022, and focus on housing and health of ASR in high-income countries. We conducted a narrative synthesis.Results: 32 studies met the inclusion criteria. The psychosocial attributes influencing health most often identified were control, followed by expressing status, satisfaction, and demand. Most attributes overlap with material/physical attributes and have an impact on ASR's mental health. They are closely interconnected with each other.Conclusion: Psychosocial attributes of housing play an essential role in the health of ASR; they are closely associated with material/physical attributes. Therefore, future research on housing and health of ASR should routinely study psychosocial attributes, but always in association with physical ones. The connections between these attributes are complex and need to be further explored.Systematic Review Registration:https://www.crd.york.ac.uk/prospero/, identifier CRD42021239495.